Manaqib al-Nūr al-Burhān and Character Education in Pesantren: A Study of Nahdlatul Ulum Boarding School Kresek - Muhamad Fauzi; Rifqi Miftahul Amili (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2026)
This study aims to describe the implementation of manaqib Syaikh Abdul Qadir al-Jailani in shaping students’ character. It also contributes to pesantren studies by demonstrating how manaqib functions not merely as a ritual practice, but as a lived pedagogical system for the internalization of Sufi-based education. In short, threse religious teachings contain spiritual, moral, and social dimensions─playing a significant role in the holistic formation of students’ character. This research employs a qualitative methodology, utilizing a hermeneutic approach to interpret the meanings and values contained in the manaqib texts, and an ethnographic approach to understand the practice of manaqib within the lived experiences of the students. Through this dual approach, the meaning of manaqib is examined both from the textual dimension and from the direct experiences of its practitioners. The findings reveal that the manaqib ritual at Nahdlatul Ulum Kresek Islamic Boarding School is conducted regularly from the 1st to the 11th of Rabīʿ al-Ākhir. The series of activities includes fasting, zikir, reading Nūr al-Burhānī, and conducting istighāsah together. Through these practices, students are guided to internalize and develop values such as patient (ṣabr), humble (tawaḍḍu’), sincerely (ikhlāṣ), intellectual attentiveness, and social responsibility. The implementation of the manaqib tradition is shown to play a significant role in strengthening the affective and spiritual dimensions of students’ character education, while simultaneously serving as a means of preserving Sufi-oriented religious traditions that constitute a distinctive identity of the pesantren.